Legal Protection of Consumers Who Experience Skin Damage Due to the Use of Illegal Skin Whitening Products Based on Law No. 8 of 1999 concerning Consumer Protection - Sitorus, Cintya Theresia A. M. (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
The existence of a beauty standard stigma that regards beauty as a condition where women have fair skin has developed into a serious issue. This stigma has emerged as a result of mass media construction and the rapid spread of foreign cultures in Indonesia. For decades, women from various parts of the world have been influenced by this stigma, leading to the emergence of an unhealthy obsession among women to possess or alter their skin color to be fair. This phenomenon is not exclusive to Indonesian women. These conditions have been exploited by entrepreneurs in the beauty and health product industry to create various types of illegal skin-whitening products. These products are manufactured and introduced to the public through advertisements with bold and misleading claims. Some of these products even claim to achieve skin whitening in a very short and safe period, despite lacking official registration numbers from the Food and Drug Monitoring Agency (BPOM), and some of them even involve falsified BPOM registration numbers. The use of these illegal skin-whitening products has caused various consumers to experience skin damage, with some cases even resulting in permanent harm. This research aims to examine the legal protection for consumers who experience skin damage due to the use of misleadingly advertised illegal skin-whitening products. Additionally, the study explores the responsibilities that should be upheld by businesses that manufacture and market these products that have detrimental effects on consumers. This research adopts an empirical legal research approach, which investigates the direct application of the law on society, legal institutions, and other relevant entities. The study is characterized as analytical-descriptive and presents a systematic analysis of facts related to legal protection for consumers facing skin damage due to the use of misleadingly advertised illegal skin-whitening products